REDD+ Crossroads Post Paris: Politics, Lessons and Interplays - Heike Schroeder (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Reducing Emissions from Deforestation and Degradation, conserving and enhancing forest carbon stocks, and sustainably managing forests (REDD+), has become a reference framework for national forest governance across many tropical and sub-tropical forest countries. These countries have used international funding to re-organize forest and conservation policy around the idea of mitigating climate change, including the development of carbon accounting protocols and national REDD+ strategies. In parallel, international conservation organizations have promoted small-scale pilot project activities, in order to capture the economic value of any resulting land-use emission reductions, mostly through voluntary carbon markets. This collection contributes with new evidence to the burgeoning research on REDD+. The first section of the collection includes eight articles that explore the politics of REDD+ design, which analyze how various governments have designed and rolled out their REDD+ strategies, and how and why a range of public and private actors become (or not) involved in such processes. These contributions explore which rationales, techniques, views and values are being contested and constructed in the design of REDD+ national strategies, which conflicts have emerged and why, or how coordination across competing actors and interests has been pursued. The second section encompasses six articles that examine the lessons of REDD+ early actions, which describe or quantify the effects of such interventions on local environments and participants' socio-economic status and cultural contexts. Finally, the third section includes five articles that explore the interplays between REDD+ and other land-use policy domains, which focus on the synergies and contradictions between the aims and policy programs conforming REDD+ national strategies and other land-use policies. Specifically, these contributions explore if REDD+ is able to improve forest sector regulations in host countries and to to align other development and land-use planning policies with REDD+ objectives and aspirations.